1999
DOI: 10.1007/pl00005321
|View full text |Cite
|
Sign up to set email alerts
|

5-HT1B receptors modulate release of [3H]dopamine from rat striatal synaptosomes

Abstract: The effect of the selective r5-HT1B agonist 3-(1,2,5,6-tetrahydro)-4-pyridil-5-pyrrolo [3,2-b] pyril-5-one (CP93,129) on the K(+)-evoked overflow of [3H]dopamine was studied in rat striatal synaptosomes loaded with [3H]dopamine. The aim of the study was to investigate the participation of 5-HT1B receptors in the serotonergic modulation of striatal dopaminergic transmission. The Ca2(+)-dependent, tetrodotoxin-resistant K(+)-evoked overflow of [3H]dopamine was inhibited by CP93,129 (0.01-100 microM) in a concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 37 publications
(52 reference statements)
1
20
0
Order By: Relevance
“…The synaptosomal preparation was obtained as described before (Sarhan et al 1999). Briefly, adult male rats, Wistar strain (Iffa Credo, l'Arbresle, France), weighing 160-200 g were sacrificed by decapitation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synaptosomal preparation was obtained as described before (Sarhan et al 1999). Briefly, adult male rats, Wistar strain (Iffa Credo, l'Arbresle, France), weighing 160-200 g were sacrificed by decapitation.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we demonstrated that 5-HT 1B heteroreceptors located on dopaminergic terminals in rat striatum, modulate the release of dopamine by inhibiting the K + -evoked overflow of [ 3 H]-DA from synaptosomes (Sarhan et al 1999). However, the functional potency of the rodent selective 5-HT 1B receptor agonist (CP93,129) to elicit this response was low (EC 50 =1.8 µM) compared to its potency to inhibit the adenylate cyclase in rat cortex (EC 50 =56 nM, Macor et al 1991), and to inhibit the K + -evoked [ 3 H]-5HT overflow from synaptosomes of rat hippocampus (EC 50 = 27 nM, Bolaños-Jiménez et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Work in striatal synaptosomes, however, suggests an inhibitory role for these receptors (Sarhan et al 1999(Sarhan et al , 2000. It is possible that an overall facilitation overshadows this inhibitory effect in vivo but requires feedback to the SN and is therefore not observed in synaptosomes.…”
Section: Nigrostriatal Pathwaymentioning
confidence: 99%
“…Building on the evidence that 5-HT1B receptors mediate motor activity as seen in the knock-out mice studies, it is also recognized that serotonin's regulatory control over dopamine neurotransmission is mediated in part by the 5-HT1B receptors. For example, Sarhan and colleagues demonstrated that 5-HT1B heteroreceptors played an inhibitory role in dopamine release in rat striatum, 17 whereas other studies have demonstrated that 5-HT1B receptors facilitate DA release in rat striatum, 18 nucleus accumbens 19 and prefrontal cortex. 20 Because serotonin modulates dopamine activity through its various receptors including 5-HT1B, these receptors can have an influence on dopaminemediated behaviours, relevant to those seen in children with ADHD.…”
mentioning
confidence: 99%